Stock Option Return Analysis at Indonesia Stock Exchange: An Empirical Study using One Touch Barrier and Black Scholes Model Period 2007 – 2011 (The Indonesian Journal of Business Administration, 2012)
Stock option is one of the option contracts which use stock as the underlying assets.Stock option itself has been traded in Indonesia at Indonesia Stock Exchange (IDX)  with  four  stocks  that  could  be  traded  for  stock options and they are PT Astra International Tbk (ASII), PT Bank Central Asia Tbk (BBCA), PT Indofood SuksesMakmurTbk (INDF), dan PT Telekomunikasi Indonesia Tbk (TLKM).Indonesia option can be considered as an American style barrier option with automatically exercise if the price hitsthe barrier level before  maturity.  Indonesia  stock  option  trading activity experienced the void trading in 2006, 2009, 2010 until 2011 and could be concluded that market is not attracted to this investment. The option exercise mechanism seems do not match with the expectation of investors. IDX should consider about other stock option trading mechanism and also other situations related to stock option that could attract market to invest in stock option. Keywords: Investment, Stock Option, One Touch Barrier, Black Scholes, Indonesian Option